Analisis Permasalahan Dalam Manajemen Perpustakaan Pusat UII (Universitas Islam Indonesia) - Iin Roikhatul Jannah; Crussita Bella, Aprilina Selly (EDUCATE : Journal of Education and Culture, 2024)
In its implementation in schools, the library has been systematically arranged in a room so that it can help students and teachers in the learning process. The UII (Indonesian Islamic University) Library provides services to users according to their needs, namely by providing excellent service in order to achieve user satisfaction. Increasingly sophisticated technology means that librarians must keep up with developments in order to know about current user needs. In particular, user visits to the library must be increased by providing encouragement first to attract users to come to the library. And in this article it is explained how important the role of library management is in the management and problems that occur in libraries, especially at the UII central library. The aim of this writing is to describe and analyze library management comprehensively. The method used in this report uses a library research method or approach, library research can be interpreted as a series or activities related to library data collection methods, reading and recording and processing research material. Library management is the effort of a school organization or library agency to achieve the goals stated in the organization's vision and mission through a process carried out jointly or in groups.